PEMBERDAYAAN UMKM DALAM PENGEMBANGAN EKONOMI LOKAL DI KABUPATEN SUMEDANG - Khoerunnisa, Adzka (JRPA - Journal of Regional Public Administration, 2025)
Empowerment of Micro, Small, and Medium Enterprises (MSMEs) has an important role in local economic development because it is able to reflect the independence and progress of a region. This study aims to obtain objective data and information regarding the empowerment of MSMEs in Sumedang Regency. The method used is qualitative with a descriptive approach. Informants are determined through purposive sampling techniques, consisting of the Head of the UMKM Division, functional positions, implementing staff, and UMKM actors. Data collection techniques include literature studies, observations, interviews, documentation, and triangulation. Data analysis is carried out through the process of reduction, presentation, and drawing conclusions. The results of the study indicate that the empowerment of MSMEs in Sumedang Regency has been going quite well. However, there are still several obstacles such as the lack of special training for personnel, inequality in the distribution of capital assistance and business protection, lack of knowledge of MSME actors, and weak communication and cooperation between related agencies and business actors. To overcome these obstacles, training and mentoring are needed to increase the capacity of MSME actors, expand access to market information and regulations, and establish regular communication forums to strengthen synergy between agencies and MSME actors. Based on these findings, it is recommended that special training be conducted for service personnel to improve professionalism, equalize assistance and business protection, and strengthen communication between the service and MSME actors. By empowering MSMEs, it is hoped that the local economy in Sumedang Regency can be developed.